EXPLORING MOTIVATION AND CLIL: A LITERATURE REVIEW - Marta del Pozo Beamud (Odisea, 2019)
In this article we intend to explore the history of motivation whithin the field of second foreign language learning. To this end, we will analyse in detail the three most important models: the Socio-educational Model, the Theory of Self-Determination and the L2 Motivational Self System. We will also analyse the relationship between motivation and CLIL, concluding that this approach is very motivating for such students, since they are more motivated than their counterparts who study English in a more traditional way (Doiz, Lasagabaster & Sierra, 2014, Seikkula-Leino, 2007).